“Homem do seu tempo e do seu país”: senhores, escravos e libertos nos escritos de Machado de Assis - Lopes, Elisângela Aparecida (Em Tese, 2008)
This article analyzes the established relations between the characters that represent masters, slaves, and freed men in Machado de Assis’ writtings. The analysis of the slavery and abolitionist themes and, above all, the identification of the discursive locus of these writings allow us to assert the writer’s involvement to the questions of his époque.